Efektivitas Komunikasi Dalam Penentuan Peneriman Program BPNT Di Desa Paku Haji Bengkulu Tengah - S, Mawan; Octaviani, Vethy; Sari, Sapta (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research aims to determine the effectiveness of communication in determining acceptance of the BPNT program in Paku Haji Village, Central Bengkulu. The research method used in this research is research presented in a qualitative descriptive manner. The selection of informants was carried out using purposive sampling. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data display and conclusion drawing and verification. Based on the research results, it can be concluded that the effectiveness of communication in receiving BPNT is effective, seen from the first competency in communication between the government and officers who are able to provide motivation to recipients about improving community welfare. Knowledge of the BPNT program, its benefits and how to use it. Communication skills in conveying messages regarding the BPNT program effectively. The two communication media are using Infocus and preparing materials such as PowerPoint and WhatsApp social media. The three languages used in formal activities are Indonesian and when communicating with BPNT recipients use regional languages so they are easy to understand.